Something that I see a lot at math competitions or on Brilliant is a problem asking to find the value of \(\sqrt{x+\sqrt{x+\sqrt{x+\ldots}}}\) for \(x=\) some value. I'm going to talk about how to solve that "nested radical" as well as "nested" fractions.

First I'm going to talk about how to solve a problem such as finding the value of \(\sqrt{6+\sqrt{6+\sqrt{6+\ldots}}}.\) Let \(k=\sqrt{6+\sqrt{6+\sqrt{6+\ldots}}}.\) You may notice that you are adding \(k\) to \(6\) and taking the square root of this. I'll demonstrate this with some parentheses. \[\sqrt{6+\sqrt{6+\sqrt{6+\ldots}}}=\sqrt{6+\left(\sqrt{6+\sqrt{6+\ldots}}\right)}=\sqrt{6+\sqrt{\left(6+\sqrt{6+\ldots}\right)}}=\ldots\] For simplicity, we're just going to use \(\sqrt{6+\sqrt{6+\sqrt{6+\ldots}}}=\sqrt{6+\left(\sqrt{6+\sqrt{6+\ldots}}\right)}.\) You may notice that this is the same thing as saying that \(k=\sqrt{6+k}.\) Let's try solving that. \[ \begin{align} k&=\sqrt{6+k}\\ k^2&=6+k\\ k^2-k-6&=0\\ (k-3)(k+2)&=0\\ k=3\text{ or }k=-2\\ \end{align} \] We can eliminate the \(k=-2\) solution because the nested radical obviously is non-negative. Thus, we can say that \(\sqrt{6+\sqrt{6+\sqrt{6+\ldots}}}=\boxed{3}.\)

Now we can use a similar line of logic to find a general form for \(\sqrt{x+\sqrt{x+\sqrt{x+\ldots}}}.\) Let that equal \(y.\) We will make use of the same procedure, but using the quadratic formula to solve for \(y.\) \[ \begin{align} y&=\sqrt{x+\sqrt{x+\sqrt{x+\ldots}}}\\ y&=\sqrt{x+y}\\ y^2&=x+y\\ y^2-y-x&=0\\ y&=\dfrac{1\pm\sqrt{1+4x}}{2}\\ \end{align} \] Since we are dealing with real numbers, the value under the radical cannot be negative (except for \(x=0\).) Thus, we can say that \(\sqrt{x+\sqrt{x+\sqrt{x+\ldots}}}=\dfrac{1+\sqrt{1+4x}}{2}.\)

Now let's use the same logic to derive a formula for nested fractions of the form \(\dfrac{1}{a+\frac{1}{a+\ddots}}\) as well as continued fractions where the numerator is not necessarily \(1.\)

First, the obligatory demonstration of such a fraction. \[ \begin{align} \dfrac{1}{2+\frac{1}{2+\ddots}}&=\dfrac{1}{2+\left(\frac{1}{2+\ddots}\right)}\\ k&=\dfrac{1}{2+k}\\ k^2+2k&=1\\ k^2+2k-1&=0\\ k&=\dfrac{-2\pm\sqrt{4+4}}{2}\\ k&=-1\pm\sqrt{2} \end{align} \] Again, we can throw out the negative solution and say that \(\dfrac{1}{2+\frac{1}{2+\ddots}}=-1+\sqrt{2}.\)

Moving on, we can derive a general formula for finding \(\dfrac{c}{x+\frac{c}{x+\ddots}},\) allowing this expression to be equal to \(y.\)

\[ \begin{align} y&=\dfrac{c}{x+\frac{c}{x+\ddots}}\\ y&=\dfrac{c}{x+y}\\ y^2+xy&=c\\ y^2+xy-c&=0\\ y&=\dfrac{-x+\sqrt{x^2+4c}}{2} \end{align} \]

So a summary of what we have proved here:

- \(\sqrt{x+\sqrt{x+\sqrt{x+\ldots}}}=\dfrac{1+\sqrt{1+4x}}{2}\)
- \(\dfrac{c}{x+\frac{c}{x+\ddots}}=\dfrac{-x+\sqrt{x^2+4c}}{2}\)

If you want some practice problems, here's two.

Find a closed form for \(x+\dfrac{1}{2x+\frac{1}{2x+\ddots}}.\)

Find all values of \(n\) for which \(\sqrt{n+\sqrt{n+\sqrt{n+\ldots}}}\) is an integer.

I hope this helps you out! Please feel free to share what you think in the comments. Thank you very much!

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestSome more nested radicals

\(\displaystyle \sqrt{x + \sqrt{x - \sqrt{x + \ldots }}} = \dfrac{1 + \sqrt{4x -3}}{2}\)

\(\displaystyle \sqrt{x - \sqrt{x + \sqrt{x - \ldots }}} = \dfrac{-1 + \sqrt{4x - 3}}{2}\)

Log in to reply

If you want to practice some problems on Nested Radicals ,

you may refer to my set Nested Radicals

Log in to reply

Thank you :)

Log in to reply

3.Let \(\sqrt{n+\sqrt{n+\sqrt{\cdots}}}=x\).Then we can write it as \(\sqrt{n+x}=x\) as you have just shown.Now solving: \[n+x=x^2\\ x^2-x-n=0\\ x=\frac{-1\pm\sqrt{(-1)^2-4(1)(-n)}}{2(1)}\\ x=\frac{-1\pm\sqrt{4n+1}}{2}\] As the nested radical is positive,so we discard the negative square root.And we are left with: \[\boxed{x=\frac{-1+\sqrt{4n+1}}{2}}\] By observation we conclude that \(4n+1\) must be a perfect square odd number.That's as far as I got.Perhaps someone could complete this.

Log in to reply

My workings are similar to yours. I think your application of the quadratic equation is wrong though. If I am mistaken please correct me!

x = [1 +sqrt(1+4n)] / 2

x is an integer when 1 + 4n is a perfect square (and positive). 1 + 4n is an odd perfect square, therefore its square root is an odd integer.

Let (y + 1)^2 = 1 + 4n y^2 + 2y + 1 = 1+ 4n 4n = y^2 + 2y n = [y^2 + 2y] / 4 = y^2/4 + y/2 y is an even integer.

Thus n is an integer, whereby for all even integers y: n = (y^2)/4 + y/2

Log in to reply

This is excellent. Thanks Trevor.

Log in to reply

Thanks dude, I'll keep your tips it in mind while solving such questions \(\ddot\smile\)

Log in to reply